2017
DOI: 10.5430/ijba.v8n7p16
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Competency on the Relationship between Training and Task Performance: Applied Study in Pharmacists

Abstract: This study aimed to determine the mediating role of competency (professional competency, technical competency, and core competency) between training and task performance in pharmacists. Questionnaire was the tool of collecting data from a sample of (210) pharmacists. The results of the study indicated that there is a positive effect of training on task performance. Also, there is full effect of the two mediator variables (professional competency; technical competency) and partial effect of the one mediator var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
2
0
1
Order By: Relevance
“…This study proved that LIPI has provided effective training for the researchers, whereas the training material, training facilitator, training methods, and training objectives were considered effective. This study finding also fits into Yang et al (2017) study, the result showed a positive role of training for improving performance. Yang et al (2017) study resulted that training has a significant influence on performance directly and could also be mediated by competency variable.…”
Section: Researchers Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…This study proved that LIPI has provided effective training for the researchers, whereas the training material, training facilitator, training methods, and training objectives were considered effective. This study finding also fits into Yang et al (2017) study, the result showed a positive role of training for improving performance. Yang et al (2017) study resulted that training has a significant influence on performance directly and could also be mediated by competency variable.…”
Section: Researchers Characteristicssupporting
confidence: 88%
“…This study finding also fits into Yang et al (2017) study, the result showed a positive role of training for improving performance. Yang et al (2017) study resulted that training has a significant influence on performance directly and could also be mediated by competency variable. This study finding also confirmed a study by Yulianto (2017) that proved training has a positive influence on performance directly and also mediated by employee satisfaction.…”
Section: Researchers Characteristicssupporting
confidence: 88%
“…Batik Trusmi Cirebon. Hasil ini dikuatkan oleh hasil penelitian penelitan Yang, J. H., Fang, S. C., & Huang, (2017) Berdasarkan fenomena permasalahan mengenai rendahnya kinerja karyawan bagian pemasaran serta adanya perbedaan hasil penelitian antara kompetensi serta motivasi terhadap kinerja, maka peneliti tertarik melakukan penelitian mengenai pengaruh kompetensi serta motivasi terhadap kinerja karyawan.…”
Section: Pendahuluanunclassified
“…The link between the independent variable "training" and dependent variables was measured in most of the studies as a one to one relation and mediating variables such "skills application" were not considered. One of the exceptions is the study by (Yang, Fang, & Huang, 2017) which demonstrated a mediating role of competencies between training and task performance and proved a significant effect of professional competency, technical competency, and core competency on the link between training and task performance. The review of empirical studies from different countries has shown that human capital and human capital analysis has been treated very differently by scientists globally.…”
Section: Empirical Studiesmentioning
confidence: 99%